Design, development, and characterization of lipid nanocarriers-based epigallocatechin gallate delivery system for preventive and therapeutic supplementation - Frias I; Neves AR; Pinheiro M; Reis S (Dove Medical Press, 2016)
Iúri Frias, Ana Rute Neves, Marina Pinheiro, Salette Reis Research Unit on Applied Molecular Biosciences, Rede de Química e Tecnologia, Departamento de Ciências Químicas, Faculdade de Farmácia, Universidade do Porto, Porto, Portugal Abstract: Green tea is manufactured from the leaves of Camellia sinensis and has been shown to possess, among other properties, anticancer, antiobesity, antiatherosclerotic, antidiabetic, antibacterial, and antiviral effects. The beneficial effects of green tea are related to the activities of (-)-epigallocatechin gallate (EGCG). This catechin is very unstable, undergoing degradation and epimerization, which is responsible for the loss of its health benefits. Encapsulation in nanoparticles (NPs) is an effective method to protect EGCG from adverse environmental conditions. In this work, solid lipid NPs (SLN) and nanostructured lipid carriers (NLC) were successfully developed to be used as biocompatible nanocarriers, enhancing the stability of EGCG. The mean diameter of the NPs was found to be around 300–400 nm, which is suitable for oral administration. Moreover, EGCG was effectively encapsulated with a remarkable efficiency of encapsulation of 80% and 90% for SLN and NLC, respectively. In addition, high storage stability of the formulations is expected as they maintain the initial characteristics for 3 months. Limited release of EGCG from the NPs was observed in simulated gastric and intestinal fluids. MTT and lactate dehydrogenase (LDH) assays demonstrated that NPs possess low toxicity, and so have potential to be used for preventive and therapeutic EGCG supplementation. Keywords: EGCG, lipid nanoparticles, nanoparticles, nutraceuticals, supplementation